2016
DOI: 10.1037/aap0000054
|View full text |Cite
|
Sign up to set email alerts
|

Big 5 personality and subjective well-being in Asian Americans: Testing optimism and pessimism as mediators.

Abstract: Understanding Asian Americans’ lives and challenges would be enhanced by examining group-specific contributors to subjective well-being (SWB). The components and predictors of SWB, as well as other dimensions of positive psychology, are understudied in mainstream psychological and Asian American literatures. The present study addressed this gap in the literature by (a) exploring multiple domains of SWB—hedonic, eudaimonic, social, physical, and financial well-being; (b) examining joint and distinct influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 71 publications
1
17
0
1
Order By: Relevance
“…Because these items were rated on different response scales, we computed their z ‐scores before creating the scale score ( α = 0.82), with higher values indicating higher levels of financial well‐being. The current scale converged strongly ( r = 0.83, N = 213) with the financial well‐being measure from Lui, Rollock, Chang, Leong, and Zamboanga () in our validation study.…”
Section: Methodsmentioning
confidence: 51%
“…Because these items were rated on different response scales, we computed their z ‐scores before creating the scale score ( α = 0.82), with higher values indicating higher levels of financial well‐being. The current scale converged strongly ( r = 0.83, N = 213) with the financial well‐being measure from Lui, Rollock, Chang, Leong, and Zamboanga () in our validation study.…”
Section: Methodsmentioning
confidence: 51%
“…This bifactor structure underlying scores justifies the use of a mean scale score to assess overall subjective well-being (Chen et al, 2013;Jovanovic, 2015). The current version of the WeBS has been validated to assess subjective well-being among Asian American samples (Lui et al, 2016).…”
Section: Differential Emotions Scale (Des;mentioning
confidence: 99%
“…These results are consistent with previous studies, such as the meta-analysis by O'Boyle et al [31] who found that EI had a significant positive relationship with "Extraversion", "Openness to experience", "Conscientiousness" and "Agreeableness", while it was the opposite with "Neuroticism". Joseph et al [30] emphasized the relationship between "Conscientiousness", "Extraversion" and Neuroticism" with EI, as did Lui et al [37], who demonstrated that "Mood" predicted wellbeing in individuals with high scores in "Extraversion", "Agreeableness" and "Conscientiousness". of According to our moderation analysis, "Neuroticism" alone would not have a significant direct effect on verbal aggressiveness.…”
Section: Discussionmentioning
confidence: 96%
“…It has likewise been shown that positiveness and optimism ("Mood") [33] favor positive interpretation of potentially stressful situations, contributing to improving their perception of their ability to control their surroundings, and thereby, their wellbeing [34][35][36]. However, the relationship between positiveness and wellbeing is stronger in persons with high scores on "Extraversion", "Agreeableness" and "Conscientiousness" [37].…”
Section: Introductionmentioning
confidence: 99%